ANALISIS KELAYAKAN USAHA DAN NILAI TAMBAH KERUPUK CUMI - Ramli Arul; Budi Setiawan; Imam Santoso; Siti Asmaul (Catholic University Musi Charitas, 2019)
One attempt to create a processed product of fishery products in the form of finished goods which main raw material are fishery products is by processing it into crackers. Crackers are generally made from tapioca flour as a source of starch with the addition of spices and water which have a low nutrient content. Addition of nutritional crackers can be done by adding fish meat. While on the other hand, the type of fish as the main raw material for making fish crackers greatly influences the color, texture and taste of fish crackers. As in the case with squid crackers which have distinctive taste and performance when compared to other fish crackers. To see the potential of the squid cracker business, it is necessary to conduct research to see whether the processing of squid into squid crackers is able to provide increased income or in other words whether the squid cracker business is feasible or not and how much added value from processing squid to squid crackers. This study aims to look at the feasibility of squid cracker business in terms of financial aspects and to determine the amount of added value obtained from processing squid into squid crackers. The research showed that the development of a squid cracker business was feasible and prospective to be carried out. The manager of squid crackers will get maximum benefits, indicated by the value of Profit (?) = 179,280,742, -per year; BEP on the basis of sales = Rp. 2.160,612,457, -; BEP on a unit basis = 60,017 kg; R / C Ratio = 1.09 (R / C> 1); Rentability = 35.02% (R> 14%) NPV = Rp. 400,130,569, - (NPV> 0); IRR = 27.57% (IRR> 14%); Net B / C = 1.58 (Net B / C ? 0); PP = 4.46 years / 53.5 months (PP <10 years). While based on value added analysis, the production of squid crackers gets an added value of Rp. 11,231 per kilogram with a value-added ratio of 41.60%, a labor compensation of Rp. 1,500, -per kilogram of raw materials, labor parts 13.36% of added value, Rp. 9,731, per kilogram and profit rate of 86.64% of added value.